Resonant power supply for high-power microwave devices - Damir R. Hafizov; Ilya N. Lobov; Leonid Y. Fetisov (Российский технологический журнал)
Objectives. The ever-increasing demands on the technical parameters of microwave radio transmission devices necessitate a search for ways of improving their efficiency and reliability, as well as means for reducing their weight and size parameters. Since such requirements largely relate to secondary power supplies, the present work set out to develop secondary power supplies for the cathode heating and bias circuits of a floating-drift multibeam klystron capable of operating at a high potential of the klystron cathode and providing stable voltage in all operating modes.Methods. In order to calculate the parameters of the resonant circuit, the first harmonic approximation method is used.Results. Approaches for designing secondary supplies are described along with the method for developing the cathode heating and bias supplies for a floating-drift multipath klystron. The calculation method used for testing the design of the transformer windings is presented. The design avoids the use of chokes as separate elements by integrating them inside a magnetic system and providing isolation by high potential of the secondary winding. The results of testing the power supply using complex test bench waveforms are given along with the main obtained parameters. The operation of the power supply is demonstrated in switching mode at zero voltage for the minimum, nominal, and maximum input voltages in the range of the inductive resistance of the circuit when the voltage phase precedes the current phase.Conclusions. The calculated efficiencies of the presented cathode heating and bias supplies are 85% and 92%, respectively. The developed supplies, which have smaller dimensions than their transformer analogues, allow a stable output voltage to be maintained when the input voltage varies, while the use of the soft start method allows the life of the klystron to be extended.